(En)gauging Self: Toward a Practical Framework for Race Talk. Issue 1 (February 2019) - Murray-Johnson, Kayon
Adult educators in higher education settings often facilitate topics that stir difficult dialogues on race and racism. In the United States, an increased population of racially diverse individuals set against the backdrop of our current sociopolitical climate, suggests the need for authentic conversations surrounding race remain critical. By extension, the need for skillful facilitators can only be expected to increase. At the same time, however, many instructors avoid or fear race talk because of its potential to become emotionally charged. This article proposes a practical, reflective framework that might be used by instructors to build emotive capacity —an important complement to instructional strategies when talking about race and racism.